2008
DOI: 10.1080/10739680701409811
|View full text |Cite
|
Sign up to set email alerts
|

Acute Leakage Patterns of Fluorescent Plasma Flow Markers after Transient Focal Cerebral Ischemia Suggest Large Openings in Blood‐Brain Barrier

Abstract: Objective: This study tested the hypothesis that blood-brain barrier (BBB) opening during acute reperfusion permits the passage of smaller macromolecules but not larger ones and that this molecular size restriction disappears over time. Methods:Following 3 hours (h) of unilateral middle cerebral artery occlusion and either 3 or 21 h of reperfusion, Wistar rats (n = 42) were injected with Evans blue (EB, a fluorescent dye that binds instantly to plasma albumin yielding EB-tagged albumin, EB-Alb) and with one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…As shown previously, significant opening of the BBB starts only 6 h after ischemia/reperfusion (Nagaraja et al, 2008;Strbian et al, 2008). Therefore, the rapid transfer of nanospheres to the brain cannot be attributed to the increased permeability of the BBB.…”
mentioning
confidence: 86%
“…As shown previously, significant opening of the BBB starts only 6 h after ischemia/reperfusion (Nagaraja et al, 2008;Strbian et al, 2008). Therefore, the rapid transfer of nanospheres to the brain cannot be attributed to the increased permeability of the BBB.…”
mentioning
confidence: 86%
“…The study concluded that the 2000 kDa dextran was too large to pass through the opening of the BBB after 3 h of reperfusion in about 40% of the microvascular networks that were visualized. 120 These studies give insight on the amount and extent of leakage that different dextrans could indicate, in regard to the disruption of particular components of the BBB. The studies indicate that selectivity in choosing a dextran size to assess BBB permeability as a result of neurotrauma is important.…”
Section: Methods Of Detection Of Vascular Changes Post-tbimentioning
confidence: 99%
“…These effects deplete energy and lead to alterations in calcium homeostasis. 120 Excess cytoplasmic calcium is taken up by various calcium buffers of the cell, such as the mitochondria. Calcium intake by mitochondria affects the mitochondrial membrane potential and when its threshold is reached, the excess calcium is pumped back into cell cytoplasm.…”
Section: What Component Of the Cerebral Vasculature Is ''Leaky''?mentioning
confidence: 99%
“…The EBDalbumin conjugate can be identified macroscopically by its striking blue color within tissue and observed by red auto-fluorescence in tissue sections examined by fluorescence microscopy [40]. Sham-operated animals or ischemic/reperfused animals were injected with 0.1 ml of 4% EBD (Sigma) in 0.9% saline through a dissected femoral vein.…”
Section: Extravasation Of Evans Blue Dye (Ebd)mentioning
confidence: 99%